Visual Analysis and Geometric Modeling of Metal Foams - Varga, Tamás Antal; Mankovits, Tamás (International Journal of Engineering and Management Sciences, 2017)
The development of an efficient procedure for 3D modelling and finite element simulation of metal foamsis one of the greatest challenges to engineer researchers nowadays. Creating 3D CAD model is alone a demandingengineering task due to its extremely complex geometry, and the proper finite element analysis process is still in thecenter of the research. The aim of this project is to analyze the related literature and to adapt the results may beconsidered.